Do ectomycorrhizal and arbuscular mycorrhizal temperate tree species systematically differ in root order-related fine root morphology and biomass? - Kubisch, Petra; Hertel, Dietrich; Leuschner, Christoph (Frontiers in Plant Science, 2015)
While most temperate broad-leaved tree species form ectomycorrhizal (EM) symbioses, a few species have arbuscular mycorrhizas (AM). It is not known whether EM and AM tree species differ systematically with respect to fine root morphology, fine root system size and root functioning. In a species-rich temperate mixed forest, we studied the fine root morphology and biomass of three EM and three AM tree species from the genera Acer, Carpinus, Fagus, Fraxinus and Tilia searching for principal differences between EM and AM trees. We further assessed the evidence of convergence or divergence in root traits among the six co-occurring species. Eight fine root morphological and chemical traits were investigated in root segments of the first to fourth root order in three different soil depths and the relative importance of the factors root order, tree species and soil depth for root morphology was determined. Root order was more influential than tree species while soil depth had only a small effect on root morphology All six species showed similar decreases in specific root length and specific root area from the 1st to the 4th root order, while the species patterns differed considerably in root tissue density, root N concentration, and particularly with respect to root tip abundance. Most root morphological traits were not significantly different between EM and AM species (except for specific root area that was larger in AM species), indicating that mycorrhiza type is not a key factor influencing fine root morphology in these species. The order-based root analysis detected species differences more clearly than the simple analysis of bulked fine root mass. Despite convergence in important root traits among AM and EM species, even congeneric species may differ in certain fine root morphological traits. This suggests that, in general, species identity has a larger influence on fine root morphology than mycorrhiza type.